O wielofunkcyjności testów w procesie poznawania lektury szkolnej = On the Multifunctionality of Tests in the Processes of School-Reading Cognition - Pańtak, Leopold (Zielona Góra: Lubuskie Towarzystwo Naukowe)
In this work there are indicated the neglects by young people in obligatory school-reading and pointed out difficulties in perception and understanding. For a number of reasons the today methods to control the knowledge of reading and to be informed about the actual didactic situation are ineffective. Even a summative evaluation after the completion of a certain stage of the subject does not satisfy this condition.
Keywords: język polski - nauczanie; testy